Comparison of Hay or Round Bale Silage as a Means to Conserve Forage - Matt Hersom; Todd Thrift; Joel Yelich (EDIS)
Florida’s climate makes conserving forages for later feeding challenging. Traditional hay harvest systems require optimal cutting, drying, and baling weather conditions. The use of round bale silage overcomes several of the challenges to hay production in Florida and offer an attractive compliment to traditional hay harvest systems. Learn more in this 6-page fact sheet written by Matt Hersom, Todd Thrift, and Joel Yelich, and published by the UF Department of Animal Science, August 2011. (Photo: Thomas Wright, UF/IFAS)